Ujicoba Hidriponik Tanaman Kencur dan Bawang Dayak - Suaibatul Aslamiah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
Indonesia has natural resources that are invaluable, especially so many medicinal plants. The purpose of this study to determine: 1) how big is the hydroponics growth the kencur and dayak onion plant without soil media, 2) the influence of nutrients and nutrient concentrations on the growth of hydroponic crops kencur and dayak onions. Benefits of this study medicinal plants in order to attract sympathy and of interest to those who had been planted in general use medium ground, so that hydroponics is an alternative cultivation techniques. The results showed that the growth of the plants hydroponically kencur less successful. Hydroponics on dayak onion plants it worked with good growth.